Results Reporting for Trials With the Same Sponsor, Drug, and Condition in ClinicalTrials.gov and Peer-Reviewed Publications - Fain, Kevin M. (JAMA Intern Med, 2018)
This study examines the extent to which trials registered in ClinicalTrials.gov by individual sponsors for the same drug and condition were available publicly in ClinicalTrials.gov and/or PubMed.